Saccharomyces cerevisiae-based platform for rapid production and evaluation of eukaryotic nutrient transporters and transceptors for biochemical studies and crystallography. - Peter Scharff-Poulsen (Public Library of Science (PLoS), 2013)
To produce large quantities of high quality eukaryotic membrane proteins in Saccharomyces cerevisiae, we modified a high-copy vector to express membrane proteins C-terminally-fused to a Tobacco Etch Virus (TEV) protease detachable Green Fluorescent Protein (GFP)-8His tag, which facilitates localization, quantification, quality control, and purification. Using this expression system we examined the production of a human glucose transceptor and 11 nutrient transporters and transceptors from S. cerevisiae that have not previously been overexpressed in S. cerevisiae and purified. Whole-cell GFP-fluorescence showed that induction of GFP-fusion synthesis from a galactose-inducible promoter at 15°C resulted in stable accumulation of the fusions in the plasma membrane and in intracellular membranes. Expression levels of the 12 fusions estimated by GFP-fluorescence were in the range of 0.4 mg to 1.7 mg transporter pr. liter cell culture. A detergent screen showed that n-dodecyl-ß-D-maltopyranoside (DDM) is acceptable for solubilization of the membrane-integrated fusions. Extracts of solubilized membranes were prepared with this detergent and used for purifications by Ni-NTA affinity chromatography, which yielded partially purified full-length fusions. Most of the fusions were readily cleaved at a TEV protease site between the membrane protein and the GFP-8His tag. Using the yeast oligopeptide transporter Ptr2 as an example, we further demonstrate that almost pure transporters, free of the GFP-8His tag, can be achieved by TEV protease cleavage followed by reverse immobilized metal-affinity chromatography. The quality of the GFP-fusions was analysed by fluorescence size-exclusion chromatography. Membranes solubilized in DDM resulted in preparations containing aggregated fusions. However, 9 of the fusions solubilized in DDM in presence of cholesteryl hemisuccinate and specific substrates, yielded monodisperse preparations with only minor amounts of aggregated membrane proteins. In conclusion, we developed a new effective S. cerevisiae expression system that may be used for production of high-quality eukaryotic membrane proteins for functional and structural analysis.